Design of Pavement Structure Based on An Empirical Mechanistic Design Approach for Roads with AC-WC Asphalt Mixture Using Buton Granular Asphalt (BGA) and Modifiers - Salsabilla, Deshafa (Bandung State Polytechnic (Politeknik Negeri Bandung), 2024)
Indonesia relies heavily on imported asphalt, consuming around 5 million tons per year, despite having substantial domestic buton granular asphalt (natural asphalt) deposits of up to 662 million tons. This research aims to analyze the potential of using buton granular asphalt B 50/30 (ASB) and a liquid asphalt modifier (SC70) as additional materials in AC-WC asphalt mixtures (AC-WC+ASB+SC70), evaluate the empirical-mechanistic design correlation, and determine flexible pavement design based on MDP 2017 method from Ministry of Public Work and Housing, Indonesia. The study employed laboratory testing using Marshall and UMATTA methods. The results showed that with the estimated bitumen content (Pb) 6%, the optimum asphalt modifier content (OMC) was 2.3%, and the UMATTA test indicated the Smix value of AC-WC+ASB+SC70 was 1202 MPa at 20°C, exceeding the typical AC-WC value of 1100 MPa. The flexible pavement design comprised a 4 cm AC-WC layer, 6 cm AC-BC layer, 18 cm AC-Base layer, and 30 cm of LPA. The findings suggest that the use of ASB and SC70 can effectively extend pavement service life. The higher the asphalt mixture's modulus value (Smix), the better the flexible pavement performance. This approach offers a sustainable solution to Indonesia's reliance on imported asphalt, leveraging its abundant domestic BGA resources.